Assessment of the Correlation between Disease Activity and Serum Biomarker Anti-MCV and IL6 in Iraqi Patients with Rheumatoid Arthritis - Ali, Dania A.; AL-Anee, Muhammad M.; Al-Anee, Nizar A.; Alrubaye, Adnan A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Rheumatoid arthritis is an autoimmune disease characterized by autoantibodies against citrullinated antigens. The anti-cyclic citrullinated peptide test is commonly used to diagnose rheumatoid arthritis, whereas the anti-mutated citrullinated vimentin is another anti-citrullinated antibody that reacts with mutated citrullinated vimentin. Anti-mutated citrullinated vimentin antibodies have been suggested as a superior early arthritis diagnostic marker. Objectives: This study aimed to evaluate the levels of IL6 and anti-mutated citrullinated vimentin biomarkers as well as to determine their potential correlation with disease activity in rheumatoid arthritis Iraqi patients. Methods: The study included an overall sample of 120 individuals who were recruited from the Department of Rheumatology at Baghdad Teaching Hospital in Baghdad, Iraq, during the period from late August 2023 to early October 2023. They were subdivided into two primary groups. The first group consisted of 60 individuals diagnosed with RA who were further categorized based on disease activity. The second group consisted of 60 healthy individuals as controls. The age range of the participants was between 20 and 79 years. An enzyme-linked immunosorbent test was used to evaluate the blood level of anti-MCV and IL-6. Results: There was no significant correlation between anti-mutated citrullinated vimentin and disease activity(p-value:0.374) also IL-6 and disease activity(p-value:0.792) but our findings showed there is a statistical accusation between Erythrocytes Sedimentation Rate, and C-reactive protein with disease activity(p-value:0.013 and 0.025) also a high positive correlation between anti-mutated citrullinated vimentin and duration of disease and anti-mutated citrullinated vimentin with Rheumatoid factor and no significant correlation between anti-mutated citrullinated vimentin and IL6. Conclusion: anti-mutated citrullinated vimentin autoantibody shows a high correlation with the duration of disease and a positive correlation with Rheumatoid factor and has no significant correlation with disease activity.